2013
DOI: 10.1002/pssa.201228731
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and high-resolution electron microscopy study of FePt L10 /A1 graded exchange spring media

Abstract: We have prepared FePt L1 0 /A1 exchange spring graded media by controlling deposition temperature. The performance of the media was determined by the deposition conditions, particularly the cooling rate. By varying the deposition conditions a coercivity of 4.0 kOe was achieved without loss in remanent magnetization, the value corresponds to 88% reduction compared with that of FePt L1 0 single phase (32.2 kOe). High-resolution transmission electron microscopy (HRTEM) investigations have revealed that this drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
5
0
1
Order By: Relevance
“…This may be responsible for spontaneous demagnetization of hysteresis loop, although a further reduction of H c (2.0 kOe) is still observed. The sequential reduction of H c with increasing t CoPt suggested that the thicker soft layers may reduce the nucleation field of the soft layer, consistent with experimental and simulated results [6,8,[12][13][14][15][16]. The in-plane hysteresis loops indicates that the graded films with t CoPt 6 20 nm exhibit perpendicular anisotropies.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This may be responsible for spontaneous demagnetization of hysteresis loop, although a further reduction of H c (2.0 kOe) is still observed. The sequential reduction of H c with increasing t CoPt suggested that the thicker soft layers may reduce the nucleation field of the soft layer, consistent with experimental and simulated results [6,8,[12][13][14][15][16]. The in-plane hysteresis loops indicates that the graded films with t CoPt 6 20 nm exhibit perpendicular anisotropies.…”
Section: Resultssupporting
confidence: 83%
“…Most of them are focused on the reduction of coercivity in conventional continuous granular structure, e.g., FePt-C [9] and FePt-TiO 2 [10], or discontinues film on single-crystal MgO or glass substrate, e.g., Fe/ FePt [11] and FePt(A1)/FePt(L1 0 ) [12][13][14]. However, the conventional granular and discontinuous film structure is not appropriate for application of BPM.…”
Section: Introductionmentioning
confidence: 97%
“…Based on these results and the existing literature [19], it is concluded that in order to successfully fabricate a hard-soft composite where magnetization is enhanced at low coercivity penalty, a low degree of exchange-coupling is desirable since it may be sufficient to align the soft spins with the hard phase without facilitating massive domain wall propagation. In that sense, the composite bilayers presented here, and associated systems with low degrees of coupling, present the advantage of a larger coercivity when compared to fully exchange-coupled systems [16,17,44,45]. However, a complete absence of coupling must be avoided, as it leads to no soft spin alignment and therefore no increase in remanence.…”
Section: Resultsmentioning
confidence: 94%
“…However, a robust exchange-coupling between hard and soft phases has been reported to lead to a quite drastic decrease in coercivity as well [15][16][17][18][19][20], as a consequence of the fast propagation of unpinned domain walls generated at the soft phase. This has been debated as a reason for some of the disappointing results obtained in the development of novel hybrid permanent magnets [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Мы полагаем, что для нашей пленки эффективная толщина слоя L1 0 -фазы увеличена за счет лежащих ниже слоев. Аналогичный эффект наблюдали в работе [18], где были совмещены эпитаксиальные слои PtFe со структурами A1 и L1 0 .…”
Section: результаты и их обсуждениеunclassified